Comparative Analysis of Capillary vs Venous Blood for Serologic Detection of SARS-CoV-2 Antibodies by RPOC Lateral Flow Tests. (28th January 2021) - Morshed, Muhammad; Sekirov, Inna; McLennan, Meghan; Levett, Paul N; Chahil, Navdeep; Mak, Annie; Carruthers, Erin; Pidduck, Tamara; Kustra, Jesse; Laley, Jonathan; Lee, Min-Kuang; Chu, Kenneth; et al.
Abstract: A comparison of rapid point-of-care serology tests using finger prick and venous blood was done on 278 participants. In a laboratory setting, immunoglobulin G (IgG) sensitivity neared 100%; however, IgG sensitivity dramatically dropped (82%) in field testing. Possible factors include finger prick volume variability, hemolysis, cassette readability, and operator training.